Comparison of gut hormones and adipokines stimulated by glucagon test among patients with type II diabetes mellitus after metabolic surgery. (February 2016) - Chen, Ying-Chieh; Inui, Akio; Chang, En-Su; Chen, Shu-Chun; Lee, Wei-Jei; Chen, Chih-Yen
Abstract: Laparoscopic Roux-en-Y gastric bypass (RYGB) achieves a higher remission of type 2 diabetes mellitus (T2DM) than laparoscopic sleeve gastrectomy (SG) in non-morbidly obese patients. However, the mechanisms of the higher remission are unknown. To compare glucagon-provoked acute insulin responses, as well as changes of gut and pancreatic hormones and adipokines between patients with T2DM after RYGB and SG at one year post-operatively, a total of 14 RYGB and 13 SG patients were followed-up and evaluated for glucose metabolism, gut and pancreatic hormones, and adipokines. One year after surgery, 1-mg intravenous glucagon tests were performed. The differences in each hormone at different time points and the area under the curve (AUC) were compared between the two groups. Glucagon-stimulated acute insulin responses were not different between the RYGB and SG groups, nor were they different between the remitters and non-remitters at one year after the metabolic surgery. Plasma des-acyl ghrelin and nesfatin-1 levels significantly decreased at 6 min after glucagon stimulation in the RYGB and SG groups, as well as in the remitters and non-remitters. The glucagon test did not affect intestinal hormones. Plasma resistin was suppressed after intravenous glucagon stimulation in both RYGB and SG groups. In conclusion, intravenous glucagon inhibited plasma levels of des-acyl ghrelin, nesfatin-1, and resistin in T2DM patients at one year after both RYGB and SG, whereas post-glucagon suppression of plasma obestatin and resistin was shown in the remitters but not in the non-remitters. Highlights: To compare post-operative gut hormones and adipokines by glucagon test in T2DM patients who underwent either RYGB or SG Intravenous glucagon inhibited plasma des-acyl ghrelin, nesfatin-1 and resistin in T2DM patients 1 year after RYGB and SG. Post-glucagon suppression of plasma obestatin and resistin was shown in the remitters but not in the non-remitters. The glucagon test did not affect intestinal hormones at 1 year after either RYGB or SG.